Characterization of plant growth promoting Diazotrophic bacteria isolated from Cacao (Theobroma cacao L.) rhizosphere treated with bamboo biochar and arbuscular mycorrhizal fungi - Cortes, Angelbert D.; Opulencia, Rina B.; Aggangan, Nelly S. (2020)
Diazotrophic bacteria (syn. nitrogen-fixing bacteria, NFB) are plant growth-promoting rhizobacteria known to facilitate nitrogen availability for plant nutrition. Biochar may serve as a refuge for colonizing microbes influencing the mycorrhizal richness and activities in the rhizosphere, thereby affecting the mycorrhization helping bacteria. This study isolated, characterized, and identified diazotrophic bacteria from the cacao (Theobroma cacao L.) rhizosphere treated with arbuscular mycorrhizal fungi (AMF) and bamboo biochar (BB). Initial screening of the cacao rhizosphere yielded 1.28x106 CFU of diazotrophic bacteria g?1 soilgrown in nitrogen-free malate medium. A total of 12 isolates were further assayed for acetylene reduction and phosphate solubilization activities. All putative diazotrophic bacterial isolates successfully reduced acetylene to ethylene gas, ranging from 16.35 ± 1.68 to 60.71 ± 2.57 ppm. Of the 12 putative diazotrophic bacterial isolates, 11 have shown phosphate solubilization activity on Pikovskaya?s medium with the solubilization index (SI) ranging from 1.12 ± 0.08 to 3.74 ± 0.16 mm. Analysis of the 16S rRNA gene sequences revealed that these diazotrophic bacterial isolates belonged to the genera Bacillus, Burkholderia, Rhizobium, and Ralstonia. These results provide evidence of candidate plant growth-promoting rhizobacteria from cacao that are potential source of biofertilizers to improve the growth and yield of cacao crops, especially in the Philippines. As agricultural options, biochar and AMF pose beneficial influence on plant growth-promoting bacteria, which primarily provide nutrients for several crops.